Calculating State-Level Estimates of Upcoming Older Adult Health Needs. Issue 4 (July 2018) - Dumont, Dora M.; Oh, Junhie; Jackson, Tracy L.; Cooper, Tara
Abstract : Objectives: Census demographers have provided projections of the increased numbers of older adults in upcoming decades, but it is less clear whether they will also be any more or less healthy than current seniors. This is critical information for state planners, as the majority of older adults will need assistance with activities of daily living to remain in their homes. Previous longitudinal and cohort studies have yielded national estimates, but those more costly sources are generally beyond the resources of state public health agencies. We provide a more practicable model for assessing state-level changes in health-related quality of life (HRQOL) among middle-aged versus older adults as a guide to probable upcoming home- and community-based service needs. Methods: We used 2 sets of state Behavioral Risk Factor Surveillance System data 15 years apart to calculate and compare adjusted odds ratios of 8 poor HRQOL measures for middle-aged and older adults. Results: Compared with their peers only 15 years earlier, recent middle-aged adults had higher odds of poor outcomes across all HRQOL measures, whereas adults 65-74 years had higher odds of poor outcomes for far fewer of the measures. Among adults 75 years and older, odds were higher compared with 15 years ago for only 1 measure (multiple days of poor mental health). Conclusions: Compared with older adults, the health profile of middle-aged adults in this state appears to have worsened much more rapidly in the past 15 years, indicating that these adults will have many more health-related needs when they become seniors. While this model is less sophisticated than others using longitudinal data, it provides the state-level data that are often more compelling to state policy makers.